Kompetensförsörjning med hänsyn till pensionsavgångar och den demografiska utvecklingen : En kvalitativ studie om kompetensförsörjning i Luleå kommun - Wikström, Anna (2011)
This is a qualitative study about human resource planning in the area concerning healthcare about elder, care about elder persons and care about persons with disabilities in the municipality of Luleå. The purpose of this study is to research and analyze how the municipality of Luleå is planning for the future, concerning healthcare about elder, care about elder persons and care about persons with disabilities, when it comes to human resource planning in competence. This is due to the fact that people are getting older which increases the amount of caretakers and lots of people in the municipality of Luleå will soon retire and a new market for private contractors has emerged. A major alternation in generation is now in process in Sweden due to a large amount of people born in the forties are now about to retire. The municipality of Luleå is up for a big challenge, both in a quantitative and qualitative perspective, when a large amount of people born in the forties and fifties are retiring. This will cause an increased demand in recruitment of personnel with the minimum of assistant nurse training. In the study, theory and concepts concerning improvement and assurance in competence and organizations have been used. Conclusions that can be drawn are that the Social Administration is working consciously with marketing different healthcare professions in different ways and by using different channels. The Social Administration is putting effort into inhouse training and they have come up with a new strategy and new methods to match the new demand concerning improvement and assurance in competence. To be considered as an attractive employer, is one important factor that the Social Administration is striving for, when they are competing on the market with private contractors. Validerat; 20110824 (anonymous)